Fibrous Myopathy as a Complication of Repeated Intramuscular Injections for Chronic Headache - R Burnham; S McNeil; C Hegedus; DS Gray (Pain Research and Management)
Two cases of fibrous myopathy associated with repeated, long-term intramuscular injections for treatment of chronic temporomandibular joint pain and chronic headache, respectively, are described. Both patients developed severe, function-limiting contractures in upper and lower extremity muscles used as injection sites. In one of the cases, the contractures were painful. Electrophysiological testing, magnetic resonance imaging and muscle biopsy results were all consistent with myopathy and replacement of skeletal muscle with noncontractile fibrous tissue. These cases are presented to increase awareness of fibrous myopathy and to promote surveillance for this serious potential complication of long-term intramuscular injections in chronic headache and other pain patients.